Biological Control of the Diamondback Moth (Plutella Xylostella Linnaeus) Using Plutella Xylostella Granulovirus - Dezianian, Ahmad (2011)
The diamondback moth (DBM) Plutella xylostella, is known to be the most serious pest of crucifers in the world. Regular and repeated use of chemical insecticides for controlling the pest over the years has resulted in DBM developing resistance to all classes of chemical insecticides. These shortcomings have prompted researchers to evaluate the potential of biological control of DBM as an alternative to conventional insecticides. One of the biological control agents is Plutella xylostella granulovirus. Plutella xylostella granulovirus (PxGV) was effective in suppressing the Malaysian population of DBM larvae. The virus was originally isolated from Taiwan and was confirmed by Restriction Endonuclease (REN) analysis. The pattern and DNA profile of the GV was compared with that of PxGV isolates reported earlier. Scanning Electron Micrograph revealed that the capsules of PxGV were ovocylindrical with a mean size of 272.84 ± 12 (length) × 148.27 ± 19 (width) nm. The virions were 168.44 ± 16 (length) × 29.57 ± 12 (width) nm and rod-shaped. Results from bioassay showed that larval mortality was significantly influenced by larval instar and viral concentrations. Mortalities caused by the highest virus concentration (3.11×109 Granules/ml) were 98.30 %, 96.60 %, 73.30 %, and 14.30 %, in the first to fourth instar, respectively. Larval mortality increased with increasing viral concentrations and decreased with the older instars. The median lethal concentration (LC50) in the second instars was estimated 1.39 × 106 Granules/ml. PxGV was susceptible to ultra violet radiation (UV) and lost almost all of its infectivity after 7 hours of exposure to UV-B radiation under laboratory conditions. Virulency of UV treated PxGV were reduced when compared to non-treated PxGV as much as 19.64%, 41.53%, 63.17%, 70% and 89 % after 5, 15, 30, 60 and 120 minutes exposure to UV radiation, respectively. Adjuvants consisting of Tinopal, molasses, lignin and skimmed milk added separately to PxGV suspension significantly improved the residual activity of PxGV after exposure to UV radiation. PxGV + Tinopal, PxGV + molasses, PxGV + lignin and PxGV + skimmed milk increased residual activity 67.78%, 65.31%, 59.55% and 31.35% after being exposed to UV radiation, respectively. The molasses and Tinopal when incorporated with different virus concentrations before exposure to UV light significantly increased the residual activity. Molasses+virus showed greatest effects on the larval mortality at all virus concentrations compared to those of Tinopal+virus and lignin+virus before exposure to UV light. The LC50 calculated for virus + molasses (5.2 × 104 Granules/ml) before exposure to UV light was 9.2 and 1.75 times lower than lignin+virus and Tinopal+virus respectively. Four spray-dried formulations were produced using a spray drying machine (Mini Spray Dryer Buchi-B 290) at concentration of 1.4 × 1010 Granules/g and coded as CLM (PxGV + modified food starch + lignin + molasses), KLM (PxGV + kaolin + lignin + molasses), CAP (PxGV + modified food starch) and KAL (PxGV + kaolin). These formulations, except KAL, caused higher larval mortality than the unformulated virus before exposure to UV light. The CLM formulation caused the highest mortality (98.60%) after exposure to UV light and significantly improved the residual activity compared to the unformulated virus. KLM, CAP, KAL formulations and control treatment provided 87.13%, 64.87%, 45.97% and 27.06% larval mortality, respectively. The LC50 values estimated for CLM formulations (1.7×105 Granules/ml) was 1.76 fold lower than KLM formulation. The results indicate that spray drying procedure did not cause adverse effects on the virus particles. The encapsulated formulation not only provided effective protection to occlusion bodies against UV radiation but it also improved biological activity of the virus as well. The spray-dried ingredients and size of microgranules considerably improved CLM formulation suspensibility. The results of semi-field tests showed that CLM formulation considerably improved residual activity of the PxGV under natural conditions. After 0.5, 5, 24, 48 and 72 hours of exposure to the natural condition, virus of the CLM formulation still retained 13.7%, 30.67%, 42.93%, 52.53% and 21.76% compared to unformulated virus, respectively. CLM formulation was significantly more effective on larval mortality than KLM formulation after exposure to natural conditions. Although spray dried formulation of PxGV was effective for controling of the pest both in the laboratory and semi-field tests, further field experiment and economical feasibility study are recommended.